A semiparametric assessment of export-led growth in the Philippines - Amrinto, Lorna E.; Zapata, Hector O. (2006)
The export-led growth (ELG) hypothesis for the Philippines is examined by adopting a semiparametric approach under two levels of temporal aggregation. To assess the impact of model specification on the ELG hypothesis, parametric and semiparametric error-correction models (ECMs)are estimated using Philippine annual and quarterly data on gross domestic product (GDP), exports, exchange rates, and gross fixed-capital formation, focusing on the role of exchange rates. The causal relationship between exports and economic growth is examined using the Granger-causality procedure. It can be concluded that for the Philippines, the elg hypothesis is (a) sensitive to model specification and (b) affected by different levels of temporal aggregation and by the inclusion or exclusion of exchange rates. The general results on bidirectional causality between exports and economic growth suggest that the Philippines could enjoy economic prosperity by strengthening its trade and investment policy and gearing it toward opening up the economy.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 20-22).
Keywords: Economic development -- Mathematical models; Exports -- Philippines